Carbon Emission Disclosure, ESG Scores, and Firm Value: Evidence from LQ45 Energy and Mining Companies - Dinda Putri Adelia; Elan Nurhadi Purwanto; Sunita Dasman (Lentera Ilmu Nusantara, 2026)
This study examines the effect of carbon emission disclosure and Environmental, Social, and Governance (ESG) scores on firm value in energy and mining companies listed in the LQ45 Index on the Indonesia Stock Exchange during the 2020–2024 period. This study employs secondary data obtained from companies’ annual reports and sustainability ratings. The sample was selected using purposive sampling, resulting in nine companies with a total of 45 firm-year observations. The data were analyzed using panel data regression with fixed-effects and generalized least squares estimations. The results indicate that carbon emission disclosure has no significant effect on firm value, whereas Environmental, Social, and Governance (ESG) scores have a significant negative effect on firm value. Simultaneously, carbon emission disclosure and Environmental, Social, and Governance (ESG) scores have a significant effect on firm value. These findings indicate that sustainability-related practices have not yet been positively reflected in market valuation, suggesting that investors may still perceive sustainability initiatives as additional costs rather than as long-term value drivers. The study concludes that the implementation of sustainability practices alone is insufficient to enhance firm value without corresponding market recognition and investor confidence.